Molecular and immunological characterization of Lp1, the 34 kDa outer membrane lipoprotein of Pseudomonas aeruginosa - Kumar A.; Naravarjula S.S.; Debnath Das M. (My University, 2025)
Polysaccharide-based vaccine for Pseudomonas aeruginosa has failed due to toxicity of lipid-A portion in liposaccharide. As a result, efforts to develop vaccine against P. aeruginosa have mostly focused on outer membrane protein (OMP). Vaccine candidates based on P. aeruginosa OMP have emerged in the form of purified recombinant protein, as alternative strategy for vaccine development. In the present study, we have determined the immunogenicity and protective capacity of Lp1 protein (as antigen). For this work we have cloned lp1 gene (897 bp) into the pET32a expression vector and after expression a 34 kDa recombinant protein was obtained by induction with 0.5 mM isopropyl β-D-1-thiogalactopyranoside. The antigen was obtained as a recombinant protein in E. coli, purified and used to immunize mice. The antiserum developed against the lp1 antigen was capable to recognize the antigen by western blotting. After immunization, recombinant Lp1 induced bactericidal antibodies. These results suggest that Lp1 is a novel antigen worth to be included in a broadly protective P. aeruginosa vaccine. © 2016 Institute of Molecular Biology, Slovak Academy of Sciences.